2006
DOI: 10.1080/09540120500456391
|View full text |Cite
|
Sign up to set email alerts
|

Does substance use moderate the effects of parents and peers on risky sexual behaviour?

Abstract: We investigated the moderating effects of drug/alcohol use in the past 3 months on the relationships of peer influence, parental permissiveness, and teen disposition (i.e., achievement motivation, attitude toward school, and value placed on health) with adolescent risky sexual behaviour. Participants were 207 adolescents receiving psychiatric care. Substance use did not moderate the relationship between adolescent disposition and risky sex. By contrast, peer influence and parental permissiveness were linked to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…In most studies, greater parental monitoring, less parental permissiveness, perceived parental warmth and support, conservative parental attitudes about sex, and frequent parent-teen communication about sex-related topics have been associated with more responsible teen sexual behavior and less sexual experience (Donenberg & Pao, 2005). Still, at least one study by teens' self-reports suggested minimal parental influence on teen sexual behavior (Beal, Ausiello, & Perrin, 2001), and one other study suggested that parental permissiveness and peer influence were only linked to risky sex among teens who reported using drugs and alcohol (Donenberg, Emerson, Bryant & King, 2006 addiction may facilitate modeling effects in children, as well as negative psychological effects (Burgess, Dziegielewski, & Green, 2005). Additional research is needed.…”
Section: Family Role Modelingmentioning
confidence: 91%
“…In most studies, greater parental monitoring, less parental permissiveness, perceived parental warmth and support, conservative parental attitudes about sex, and frequent parent-teen communication about sex-related topics have been associated with more responsible teen sexual behavior and less sexual experience (Donenberg & Pao, 2005). Still, at least one study by teens' self-reports suggested minimal parental influence on teen sexual behavior (Beal, Ausiello, & Perrin, 2001), and one other study suggested that parental permissiveness and peer influence were only linked to risky sex among teens who reported using drugs and alcohol (Donenberg, Emerson, Bryant & King, 2006 addiction may facilitate modeling effects in children, as well as negative psychological effects (Burgess, Dziegielewski, & Green, 2005). Additional research is needed.…”
Section: Family Role Modelingmentioning
confidence: 91%
“…10,68 Some studies suggest that for families residing in impoverished urban environments, other factors such as caregiver substance use may be more important predictors of youth sexual risk than the caregiver-youth relationship. 24,26 Alternatively, youth-caregiver relationship factors were based on caregiver and not youth response, and may not accurately reflect the quality of the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Thus, their children are also at risk for psychiatric and substance use disorders due to genetic and environmental pathways previously described in other populations. 23 All of the above factors, including caregiver mental illness and substance abuse, 24,25 disrupted family relationships and functioning, [26][27][28] and youth mental health and substance use problems 10,[29][30][31][32] have been associated with sexual risk behaviors in various adolescent populations. Thus, taken together, individual and contextual factors place PHIV + youth at elevated risk for behaviors that may lead to poor individual (re-infection of resistant strains of the virus, STIs, and unplanned pregnancy) and public health (transmission to partners) outcomes.…”
mentioning
confidence: 99%
“…The majority of research findings among college students suggest that a high level of HIV and STD risk behavior is associated with inconsistent or lack of condom use, multiple lifetime sex partners, and alcohol and other drug use combined with sexual activity (Catania, Coates, Stall, Turner et al, 1992;Donenberg, Emerson, Bryant & King, 2006;Lewis & Malow, 1997). The Center for Disease Control (CDC), in the National College Health Risk Survey, indicated that 35% of college students ages 18-24 had had six or more sexual partners in their lifetime, only 25% reported consistent condom use with their partner, and 17 % of college students polled had used alcohol or drugs during their last sexual encounter (CDC, 1997).…”
Section: Review Of Literaure Young Adults and Sexual Risk Taking Behamentioning
confidence: 99%